Observasi Observasi Pelaksanaan SKP Ke-3 dengan Pendekatan 6 Benar pada Pasien dengan Anemia + Hepatomegali Di Ruang Perawatan C (RPC) RSU Kaliwates Jember - Erika Wulandari; Alfid Tri Afandi; Anisah Ardiana; Denny Rifki Kurniawan (KHD Production, 2025)
Patient safety is a process related to healthcare facilities that serve patients safely. The global issue of patient safety in health services is an important factor in certifying that hospitals can provide maximum service following Standard Operating Procedures (SOP) to ensure patient safety by the principles of patient safety. The application of the principle of correct medication administration is something that must be considered to minimize patient safety events that can cause harm to patients, health workers, or hospitals. This study aimed to analyze medication administration with the six rights medication principles implemented by nurses in cases of anemia and hepatomegaly in Treatment Room C (RPC) RSU Kaliwates Jember. This type of research is quantitative, using a descriptive analysis case study approach. The results showed that the average total percentage related to applying the six rights principles of medication administration was 70%. The percentage of each indicator includes correct medication (84.62%), correct dose (38.46%), correct time (80.77%), correct patient (65.38%), correct route (61.54%), and correct documentation (66.67%). Based on these results, it is not optimal because the application of the six rights principles of medication administration has not reached a percentage of 100%. Health agencies must update strategies to improve nurse compliance in applying the six rights principles of medication administration.